Increased arachidonic acid composition of phospholipids in colonic mucosa from patients with active ulcerative colitis. Issue 8 (August 1987) - Nishida, T; Miwa, H; Shigematsu, A; Yamamoto, M; Iida, M; Fujishima, M
Abstract : The long chain fatty acid composition of phospholipids in colonic mucosa was determined by high performance liquid chromatography in nine patients with active ulcerative colitis and eight healthy controls. The arachidonic acid composition was 12.5 +/- 1.4 mol % (mean +/- 2 SEM) in the inflamed colonic mucosa from the patients with active ulcerative colitis and 6.8 +/- 1.2 mol % in the intact mucosa from healthy controls (p less than 0.001). In the inflamed colonic mucosa, oleic acid and palmitoleic acid were concomitantly decreased (p less than 0.001 and p less than 0.02, respectively), while docosahexaenoic acid was increased (p less than 0.05). Histopathological examination showed that there was a three fold increase in the cell density of inflammatory infiltrate in the lamina propria of the inflamed colonic mucosa (p less than 0.001). The cell density of inflammatory infiltrate correlated with the arachidonic acid composition of phospholipids in colonic mucosa (r = 0.89, p less than 0.005). These findings indicate that inflammation alters the long chain fatty acid composition of phospholipids in colonic mucosa. The observed increase in the arachidonic acid composition of phospholipids in inflamed colonic mucosa may contribute to the enhanced arachidonic acid metabolism in patients with active ulcerative colitis.